1998
DOI: 10.1042/bj3290175
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and chemical mechanisms for the effects of univalent cations on the spectral properties of aromatic amine dehydrogenase

Abstract: Univalent cations and pH influence the UV-visible absorption spectrum of the tryptophan tryptophylquinone (TTQ) enzyme, aromatic amine dehydrogenase (AADH). Little spectral perturbation was observed when pH was varied in the absence of univalent cations. The addition of alkali metal univalent cations (K+, Na+, Li+, Rb+ or Cs+) to oxidized AADH caused significant changes in its absorption spectrum. The apparent Kd for each cation, determined from titrations of the spectral perturbation, decreased with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…However, we demonstrated that this was not possible owing to rapid reduction of the TTQ cofactor by the buffer components. Also, as noted previously, univalent cations stimulate spectral changes in AADH, particularly at higher pH values [20] and our own studies revealed a similar trend at higher pH values with various univalent cations (data not shown). Thus, owing to a rapid loss in absorbance at 456 nm (attributed to chemical modification of the TTQ to form an hydroxide adduct) [20], it was not feasible to perform pH-dependent studies of TTQ reduction in the presence of added salt (although studies performed in the presence of 100 mm NaCl at lower pH values yielded results comparable with those obtained in the absence of NaCl).…”
Section: Ph Dependence Of Ttq Reduction With Benzylamine and Deuteratsupporting
confidence: 88%
“…However, we demonstrated that this was not possible owing to rapid reduction of the TTQ cofactor by the buffer components. Also, as noted previously, univalent cations stimulate spectral changes in AADH, particularly at higher pH values [20] and our own studies revealed a similar trend at higher pH values with various univalent cations (data not shown). Thus, owing to a rapid loss in absorbance at 456 nm (attributed to chemical modification of the TTQ to form an hydroxide adduct) [20], it was not feasible to perform pH-dependent studies of TTQ reduction in the presence of added salt (although studies performed in the presence of 100 mm NaCl at lower pH values yielded results comparable with those obtained in the absence of NaCl).…”
Section: Ph Dependence Of Ttq Reduction With Benzylamine and Deuteratsupporting
confidence: 88%
“…Type I causes a red shift of the oxidized spectrum of MADH, whereas type II causes a bleaching of the visible spectrum and an increased absorbance in the near ultraviolet, similar to that observed during reduction of the enzyme by methylamine. Analogous spectral perturbations have been observed with another TTQcontaining enzyme, aromatic amine dehydrogenase (21). The type I binding site is specific for larger cations such as Cs ϩ , Rb ϩ , and NH 4 ϩ as well as di-, tri-, and tetramethylammonium ions.…”
supporting
confidence: 54%
“…MADH and amicyanin concentrations were calculated from known extinction coefficients (3,14) in 10 mM phosphate buffer, pH 7.5. The extinction coefficients of the different redox forms of MADH vary with pH (20) and ionic composition of the buffer (21). Purifications of AADH (7) and azurin (8,22) from A. faecalis (IFO 14479) were as described previously, and protein concentrations were calculated from previously determined extinction coefficients (7,23).…”
Section: Methodsmentioning
confidence: 99%
“…The only difference was that the rate of the disproportionation reaction of AADH was faster than that of MADH. The extinction coefficients for the different redox states of MADH and AADH vary with pH in the presence of monovalent cations (20,21). For this reason, BTP buffer was used.…”
Section: Figmentioning
confidence: 99%